THE WOMAN'S CONCEPTION PORTRAYED BY DIFFERENT MUSICAL GENRES: RESEARCH PROPOSAL IN IDENTITY POLICIES AND POLITICAL IDENTITIES - Godoy, Diego Azevedo [UNESP]; Rossi, Celia Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This work is the proposal of a research project that is based from the perspective of Social Psychology Dialectic of Lane (1984), through authors such as Goffman (1977), (2004), Ciampa (1977), (2002), Honneth (2003), Habermas (1983) and especially the theory of the assumptions of the author's identity mentioned above Ciampa (2007). This study focuses on the search for understanding of how women are portrayed by different styles and music genres, in Brazil. The qualitative methodology begins with a study through an historical and bibliographical perspective lifting of works published data, so the methodology undergoes a second stage, where the field will be interviews narratives professional life stories of musicians of different genres studied, in order to obtain an active listening of one's female author who builds/portrays the feminine in his music. Giving emphasis to the studies of Identity Policies and Identity Policies.
Keywords: Identity; Political identity; Music; Female